2006
DOI: 10.1256/qj.05.183
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the wavelength dependence of the aerosol optical depth in the Athens area

Abstract: SUMMARYGround-based solar spectral irradiance measurements obtained by a spectroradiometer have been used to retrieve the aerosol optical depth, τ α , and theÅngström wavelength exponent, α. These measurements were obtained in the Athens centre in May 1995. Exponent α is frequently computed from spectral measurements both from ground-based photometers and satellite remote sensing retrievals. Although the retrieval of α has been the subject of many studies worldwide, its spectral variation is typically not cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 59 publications
9
51
0
5
Order By: Relevance
“…The sun-photometer provides optical depths by knowing the respective radiation intensities at topof-atmosphere (TOA), using its internal calibration. The errors in the AOD estimations were found to be well below, or equivalent, to ±0.03 (Morys et al, 2001) with larger values in the UV, while errors from the subtraction of Rayleigh component, ozone and water-vapor absorption are about one order of magnitude lower (Kaskaoutis and Kambezidis, 2006). As discussed by Kaskaoutis et al (2010), we followed the method outlined by Cachorro et al (2004) for correction of AOD at each wavelength in order to eliminate the diurnal artifact of AOD.…”
Section: Ship-borne Measurements and Methodologymentioning
confidence: 99%
“…The sun-photometer provides optical depths by knowing the respective radiation intensities at topof-atmosphere (TOA), using its internal calibration. The errors in the AOD estimations were found to be well below, or equivalent, to ±0.03 (Morys et al, 2001) with larger values in the UV, while errors from the subtraction of Rayleigh component, ozone and water-vapor absorption are about one order of magnitude lower (Kaskaoutis and Kambezidis, 2006). As discussed by Kaskaoutis et al (2010), we followed the method outlined by Cachorro et al (2004) for correction of AOD at each wavelength in order to eliminate the diurnal artifact of AOD.…”
Section: Ship-borne Measurements and Methodologymentioning
confidence: 99%
“…For example, parameters like aerosol optical depth (AOD), the Ångström exponent (AE), aerosol loading, and particle effective radius and different viewing angles are used to depict information regarding aerosol dominant types, emission sources, dust layers, and trajectories Kaskaoutis and Kambezidis, 2006;Agarwal et al, 2007;Gobbi et al, 2007;Kalapureddy and Devara, 2008;Russell et al, 2010). Analyzing the derivatives of the AE and particle effective radius is also used to attain information regarding aerosol sizes and types since the particle types are directly correlated with sizes and optical properties (Gerasopoulos et al, 2003(Gerasopoulos et al, , 2011Alados-Arboledas et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Eck et al, (1999;2001) and Ranjanet al,( 2007) reported that large positive values of Ångström exponent  are characteristics of fine-mode-dominated aerosols size distributions while near zero and negative values are characteristics of dominant coarse-mode or bi-modal size distributions, with coarse-mode aerosols having significant magnitude (Eck et al, 1999;O'Neill et al, 2001;Kaskaoutis and Kambezidis, 2006). In case of negative curvature (α2<0, convex type curves) the rate of change of α is more significant at the longer wavelengths, while in case of positive curvature (α2>0, concave type curves) the rate of change of α is more significant at the shorter wavelengths (Kaufman, 1993;Eck et al, 1999;Eck.…”
Section: Resultsmentioning
confidence: 99%